Structural Posterior Fossa Malformations: MR Imaging and Neurodevelopmental Outcome - Jorden Halevy; Hadar Doitch Amdurski; Michal Gafner; Shalev Fried; Tomer Ziv-Baran; Eldad Katorza (Diagnostics)
Objectives: The increasing use of fetal MRI has increased the diagnosis of posterior fossa malformations, yet the long-term neurodevelopmental outcomes of affected fetuses remain unclear. This study aims to examine the long-term neurodevelopmental outcomes of fetuses with structural posterior fossa malformation diagnosed on fetal MRI. Methods: A historical cohort study was conducted at a single tertiary referral center, including fetuses diagnosed with structural posterior fossa malformations and apparently healthy fetuses who underwent fetal brain MRI between 2011 and 2019. Maternal, pregnancy, and newborn characteristics were compared between groups, alongside long-term neurodevelopmental outcomes using the Vineland Adaptive Behavior Scales II (VABS-II) questionnaire. This included an extensive assessment of malformation types, additional structural, genetic, or neurodevelopmental anomalies, and outcomes. Results: A total of 126 fetuses met the inclusion criteria, of which 70 were apparently healthy fetuses, and 56 had structural posterior fossa malformations. Among the latter, 18 pregnancies were terminated, 4 resulted in neonatal death, and 11 were lost to follow-up. No significant differences were found in the overall neurodevelopmental outcomes between fetuses with structural posterior fossa malformation (93.4 ± 19.0) and apparently healthy fetuses (99.8 ± 13.8). Motor skills scores were lower among fetuses with structural posterior fossa malformations (87.7 ± 16.5 vs. 99.3 ± 17.2, p = 0.01) but remained within the normal range. Conclusion: Fetuses with structural posterior fossa malformations may exhibit normal long-term neurodevelopmental outcomes if no additional anomalies are detected during thorough prenatal screening that includes proper sonographic, biochemical and genetic screening, as well as fetal MRI. Further research with larger cohorts and longer-term assessments is recommended to validate these findings and support clinical decision-making.